Monostotic fibrous dysplasia in a 10-year-old patient - Gayatri Nayanar; Mamatha G S. Reddy (Wolters Kluwer Medknow Publications, 2021)
Fibrous dysplasia is a rare congenital bone disorder which manifests as a localized defect in osteoblastic differentiation and maturation with the replacement of normal bone with an abnormal scar-like fibrous connective tissue. It can be classified into monostotic and polyostotic variety with the former seen mostly in the adults and the latter common in children. Craniofacial involvement in case of fibrous dysplasia is very common, affecting maxilla more commonly than the mandible. This report, however, describes a case of fibrous dysplasia in a 10-year-old female patient who presented with a swelling of the left mandible.